2022
DOI: 10.1186/s40337-022-00711-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between early maladaptive schemas, temperament and eating attitude in adults

Abstract: Background Current research on eating attitude has focused primarily on female perspective (Kapoor et al. in J Educ Health Promot 11(80):1–7, 2022; Piko et al. in J Prev Med Hyg. 63(1):83–89, 2022). To extend cross-gender approaches, this study aimed to examine the relationship between early maladaptive schemas, temperament, and eating attitude and to see whether these three concepts differ between men and women. Methods The sample group consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Early Maladaptive Schemas are described as persistent themes developed during childhood, and elaborated on throughout the life course, based on experiences regarding oneself and one’s relationships with others, especially within a hostile, critical, abusive, and neglectful environment [ 27 ]. Unsatisfied core needs, which are inadequate for the purpose of the child’s healthy development in their early environment, can be grouped into five domains: disconnection and rejection (formed as a result of experiences of abusive, unaffectionate or unstable family systems), impaired autonomy and performance (which is a result of excessive parental attention or no regard at all), impaired limits (which is a result of an overly liberal family environment), other directedness (effect of conditional love and acceptance from caretakers), and over-vigilance and inhibition (which are the result of a harsh parental approach) [ 97 ]. Coping Styles are used to describe the ways an individual adapts to the environment, and include three main strategies: overcompensation (behaving opposite to the schema), surrendering (acting according to the schema), and avoidance (avoiding schema activation).…”
Section: Schema Therapy As An Alternative Treatment Methods For Adole...mentioning
confidence: 99%
“…Early Maladaptive Schemas are described as persistent themes developed during childhood, and elaborated on throughout the life course, based on experiences regarding oneself and one’s relationships with others, especially within a hostile, critical, abusive, and neglectful environment [ 27 ]. Unsatisfied core needs, which are inadequate for the purpose of the child’s healthy development in their early environment, can be grouped into five domains: disconnection and rejection (formed as a result of experiences of abusive, unaffectionate or unstable family systems), impaired autonomy and performance (which is a result of excessive parental attention or no regard at all), impaired limits (which is a result of an overly liberal family environment), other directedness (effect of conditional love and acceptance from caretakers), and over-vigilance and inhibition (which are the result of a harsh parental approach) [ 97 ]. Coping Styles are used to describe the ways an individual adapts to the environment, and include three main strategies: overcompensation (behaving opposite to the schema), surrendering (acting according to the schema), and avoidance (avoiding schema activation).…”
Section: Schema Therapy As An Alternative Treatment Methods For Adole...mentioning
confidence: 99%
“…Unaddressed EMSs, activated in adulthood, can lead to a wide range of mental health problems, such as anxiety, depression, or personality disorders (Bilge & Balaban, 2021;Güler & Özgörüş, 2022;Jain & Singh, 2022;Shorey, Stuart, & Anderson, 2014;Stavropoulos et al, 2020). However, EMSs can be addressed through psychotherapy; e.g., cognitive-behavioral therapy (CBT), including schema therapy, which might help individuals identify and challenge their negative schemas and develop more adaptive ways of thinking, feeling, and behaving (Young, 2014).…”
Section: Early Maladaptive Schemasmentioning
confidence: 99%
“…Some studies explored links between EMSs and personality traits in clinical and non-clinical samples. The findings revealed that while the links between EMSs and personality traits are more or less evident in clinical samples (Bilge & Balaban, 2021;Esmaeilian et al, 2019;Güler & Özgörüş, 2022;Pauwels et al, 2016;Shojaati, Kalantari, & Mulavi, 2019;Shorey, Stuart, & Anderson, 2014;Yığman et al, 2021), the associations between EMSs and personality traits in healthy individuals need deeper investigation. This research aimed to explore the links between EMSs and personality traits in healthy individuals (without a clinical diagnosis of mental illness).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Females are dispropor-tionately affected by EDs and, compared with male counterparts, report greater severity of ED symptoms [ 3 , 4 ]. Indeed, females generally report greater cognitive vulnerability in terms of early maladaptive schemas compared with males [ 5 , 6 ] and in association with sexual and marital dissatisfaction [ 7 , 8 ] as well as in association with eating attitudes [ 1 ]. While the empirical relationship between maladaptive cognitions such as negative self-beliefs and ED symptoms has been extensively supported in females with EDs [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] the assessment of functional adaptive beliefs regarding the self, others, and the world in this clinical population is frequently ignored [ 14 , 18 ].…”
Section: Introductionmentioning
confidence: 99%